A cross-sectional survey of nursing students' patient safety knowledge. (May 2020) - Levett-Jones, Tracy; Andersen, Patrea; Bogossian, Fiona; Cooper, Simon; Guinea, Stephen; Hopmans, Ruben; McKenna, Lisa; Pich, Jacqui; Reid-Searl, Kerry; Seaton, Philippa
Abstract: Background: Knowledge provides a foundation for safe and effective nursing practice. However, most previous studies have focused on exploring nursing students' self-reported perceptions of, or confidence in, their level of patient safety knowledge, rather than examining their actual levels of knowledge. Objective: The overarching objective of this study was to examine final year nursing students' levels of knowledge about key patient safety concepts. Design: A cross-sectional design was used for this study. Data collection was undertaken during 2018 using a web-based patient safety quiz with 45 multiple choice questions informed by the Patient Safety Competency Framework for Nursing Students. A Modified Angoff approach was used to establish a pass mark or 'cut score' for the quiz. Setting and participants: Nursing students enrolled in the final year of a pre-registration nursing program in Australia or New Zealand were invited to participate in the study. Results: In total, 2011 final year nursing students from 23 educational institutions completed the quiz. Mean quiz scores were 29.35/45 or 65.23% (SD 5.63). Participants achieved highest scores in the domains of person-centred care and therapeutic communication, and lowest scores for infection prevention and control and medication safety. Based on the pass mark of 67.3% determined by the Modified Angoff procedure, 44.7% of students (n = 899) demonstrated passing performance on the quiz. For eight of the institutions, less than half of their students achieved a passing mark. Conclusions: Given the pivotal role that nurses play in maintaining patient safety, the results from this quiz raise important questions about the preparation of nursing students for safe and effective clinical practice. The institutional results also suggest the need for increased curricula attention to patient safety.